Immune-related gene signatures of thin endometrium: a transcriptomic and single-cell study - Niu, Yifei; Le, Aiwen (Frontiers in Endocrinology, 2025)
BackgroundThin endometrium (TE) is associated with impaired endometrial receptivity and reduced rates of successful pregnancy. However, the immune-related transcriptomic alterations underlying TE remain poorly understood. This study aimed to identify differentially expressed genes (DEGs) and immune signatures associated with TE using integrated transcriptomic approaches.ResultsBulk RNA sequencing of endometrial tissues from TE patients and healthy controls revealed 57 DEGs. Gene Ontology enrichment analysis revealed the involvement of immune activation processes including leukocyte degranulation and natural killer (NK) cell-mediated cytotoxicity. Integration with publicly available single-cell RNA-seq data confirmed increased immune cell infiltration and altered gene expression in stromal and epithelial cell populations. Notably, significant upregulation of CORO1A, GNLY, and GZMA was observed in both datasets and validated using quantitative PCR. These genes are functionally related to cytotoxic immune responses. Canonical senescence markers were not detected, suggesting that immune dysregulation may play a more prominent role than senescence in TE pathogenesis.ConclusionsThis study provides transcriptomic evidence that TE is associated with immune-related alterations, particularly those involving cytotoxic gene activation. The identified genes may serve as potential biomarkers or therapeutic targets for improving endometrial receptivity. These findings offer new insights into the molecular mechanisms of TE and lay the groundwork for future functional investigations.Clinical Trial RegistrationInstitutional Review Board Statement: This study was approved by the Ethics Committee of Shenzhen Nanshan Hospital (formerly known as Union Shenzhen Hospital of Huazhong University of Science and Technology at the time of ethical approval), under ethics approval number 072652 (approval date: 26 July 2019). The study was also registered with the China Clinical Trial Registration Center under registration number ChiCTR2000038068. The study was conducted in accordance with the Declaration of Helsinki.